Crude glycerol negatively affects rabbit spermatozoa motility in vitro - PAAL, D.; STREJCEK, F.; SLANINA, T.; KOVACOVA, R.; LUKAC, N.; QOJA, A. O.; ONDRUSKA, L.; FORMICKI, G.; TVRDA, E.; MASSANYI, P. (Journal of the Hellenic Veterinary Medical Society, 2018)
In recent years the conventional diet for farmed animals has been increasingly substituted by alternative energy sources such as crude glycerol. There is an urgent need for investigation of the impact of crude glycerol on the male reproductive tract. Rabbit semen was cultured in a TRIS/NaCl-based medium containing 0% (control), 5%, 10%, 15% and 20% crude glycerol. Sperm kinetic characteristics were assessed immediately and 30 min, 60 min, 120 min and 180 min upon treatment by computer assisted analyzer. In general, a decrease in motility was recorded for the spermatozoa treated with 5% glycerol (P<0.001). A substantial reduction in spermatozoa motility was observed in the samples containing 10% and 15% crude glycerol (P<0.05). The lowest motility was observed for spermatozoa incubated with 20% crude glycerol. Presented data suggest toxic effects of crude glycerol on the rabbit spermatozoa kinetics in vitro.